Predictive Value of Hepatorenal Status in Contrast-Induced Nephropathy Among Patients Receiving Coronary Angiography and/or Intervention: A Systematic Review and Meta-Analysis. (August 2019) - Zhang, Enyuan; Lu, Yaru; Chen, Gang; Huang, Lingyu; Zhang, Jingkun; Wang, Chengjian; Qin, Qin
Background: Low serum albumin, high blood urea nitrogen (BUN), and uric acid are regarded closely related to the incidence of contrast-induced nephropathy (CIN), whereas it remains unclear whether they can function as predictors of CIN onset. The objective of this systematic review and meta-analysis was to explore the association between abovementioned indicators and CIN incidence rate in patients receiving coronary angiography (CAG) and/or intervention. Methods: Clinical studies were retrieved from the electronic databases of PubMed, EMBASE, Google Scholar, Clinical Trials, and ScienceDirect from their inception to July 13, 2018. Meta-analysis was performed on pooled eligible studies to determine whether these hepatorenal indicators were associated with CIN. Results: A total of 18 studies involving 16 171 patients were included in the meta-analysis. Pooled analysis results revealed that patients with hypoalbuminemia (odds ratio [OR] = 3.09, 95% confidence interval [CI] = 1.44-6.64, P = .004) and hyperuricemia (OR = 1.32, 95% CI = 1.15-1.50, P < .0001) both exhibited significantly higher CIN rates, regardless of the study design, renal function, and whether urgent clinical situation or not. However, there was no significant association between serum BUN and CIN risk. Conclusion: Hypoalbuminemia and hyperuricemia are independently associated with the occurrence of CIN among the patients undergoing CAG and/or intervention.